“Everything Will Be All Right!” National and European Identification as Predictors of Positive Expectations for the Future During the COVID-19 Emergency - Moscatelli, Silvia; Graziani, Anna Rita; Botindari, Lucia; Ciaffoni, Stefano; Menegatti, Michela (Frontiers in Psychology, 2021)
During the first national lockdown imposed in a Western country to reduce the impact of the COVID-19 pandemic, many Italians tried to boost their spirits by hanging hand-drawn rainbows with the slogan “Everything will be all right” from their windows. To understand which processes might have nurtured their positive views about the future during the pandemic, the present study (N=846), building upon social identity research, examined the relationships among Italians’ identification with their country and with the superordinate entity of the European Union (EU), trust in the main institutions in charge of managing the crisis (i.e., the Italian government, the EU, and the scientific community), and beliefs that the COVID-19 crisis would eventually result in the improvement of society. Structural equation modeling analyses showed that identification with Italians and Europeans had positive direct associations with positive expectations about humankind. Identification with Europeans was also directly related to positive expectations about Italian leaders and the strengthening of the EU through the crisis. Trust in the Italian government and, to a lower extent, trust in the EU mediated some of these associations. These findings suggest that governments should actively promote national and European identification to help citizens counter the negative psychological impact of the pandemic and maintain positive views of the future.